The effects of psychoeducational family intervention on coping strategies of relatives of patients with bipolar I disorder: results from a controlled, real-world, multicentric study - Sampogna G (Dove Medical Press, 2018)
Gaia Sampogna,1 Mario Luciano,1 Valeria Del Vecchio,1 Claudio Malangone,1,2 Corrado De Rosa,1 Vincenzo Giallonardo,1 Giuseppina Borriello,1 Benedetta Pocai,1 Micaela Savorani,1 Luca Steardo Jr,1 Debora Lampis,3 Franco Veltro,4 Francesco Bartoli,5 Francesco Bardicchia,6 Anna Maria Moroni,7 Giusy Ciampini,8 Emanuele Orlandi,9 Silvia Ferrari,10 Silvia Biondi,11 Sonia Iapichino,11,12 Enrico Pompili,13 Massimiliano Piselli,14 Alfonso Tortorella,15 Giuseppe Carrà,5,16 Andrea Fiorillo1 1Department of Psychiatry, University of Campania “Luigi Vanvitelli”, Naples, 2Mental Health Centre of Ravello, Mental Health Unit, Ravello, 3Mental Health Centre of Lanusei, Mental Health Unit, Lanusei, 4Mental Health Department of Campobasso, Campobasso, 5Department of Medicine and Surgery, University of Milano Bicocca, Monza, 6Mental Health Centre of Grosseto, Mental Health Unit, Grosseto, 7Niguarda Hospital, Department of Psychiatry, Milan, 8Mental Health Centre of Lanciano, Mental Health Unit, Lanciano, 9Mental Health Centre of Sassuolo, Mental Health Unit, Sassuolo, 10University of Modena and Reggio Emilia, Department of Psychiatry, Reggio Emilia, 11Mental Health Centre of Montecatini, Mental Health Unit, Montecatini, 12Auditor Psychiatrist, for the activities of Clinical Risk Management and safety of treatments, Tuscany Region, 13Mental Health Centre of Rome, Mental Health Unit, Rome, 14Mental Health Centre of Foligno, Mental Health Unit, Foligno, 15Department of Medicine, Section of Psychiatry, University of Perugia, Perugia, Italy; 16Division of Psychiatry, University College of London, London, UK Background: Psychoeducational family intervention (PFI) has been proven to be effective in improving the levels of family burden and patients’ personal functioning in schizophrenia and bipolar disorders (BDs). Less is known about the impact of PFI on relatives’ coping strategies in BD. Methods: A multicenter, controlled, outpatient trial funded by the Italian Ministry of Health and coordinated by the Department of Psychiatry of the University of Campania “Luigi Vanvitelli” has been conducted in patients with bipolar I disorder (BD-I) and their key relatives consecutively recruited in 11 randomly selected Italian community mental health centers. We aim to test the hypothesis that PFI improves problem-oriented coping strategies in relatives of BD-I patients compared to the Treatment As Usual (TAU) group. Results: The final sample was constituted of 123 patients and 139 relatives. At baseline assessment (T0), the vast majority of relatives already adopted problem-oriented coping strategies more frequently than the emotion-focused ones. At the end of the intervention, relatives receiving PFI reported a higher endorsement of adaptive coping strategies, such as “maintenance of social interests” (odds ratio [OR]=0.309, CI=0.04–0.57; p=0.023), “positive communication with the patient” (OR=0.295, CI=0.13–0.46; p=0.001), and “searching for information” (OR=0.443, CI=0.12–0.76; p=0.007), compared to TAU relatives, after controlling for several confounders. As regards the emotion-focused coping strategies, relatives receiving the experimental intervention less frequently reported to adopt “resignation” (OR=-0.380, CI=-0.68 to -0.08; p=0.014) and “coercion” (OR=-0.268, CI=-0.46 to -0.08; p=0.006) strategies, compared to TAU relatives. Conclusion: PFI is effective in improving the adaptive coping strategies of relatives of BD-I patients, but further studies are needed for evaluating the long-term benefits of this intervention. Keywords: coping strategies, family burden, psychoeducation family intervention, bipolar disorder, social functioning